Red and Coldness: Wives and Concubines by Su Tong and Zhang Yimou’s Raise the Red Lantern - Aleksandrowicz, Joanna (Media - Culture - Social Communication, 2020)
In this article, adaptive strategies in Zhang Yimou’s film Raise the Red Lantern (1991), based on Su Tong’s story Wives and Concubines are depicted. A game between what is shown and what is hidden is analysed in the context of the concept of void in oriental aesthetics and the compositional frame in scenography and in narration. The film follows the rhythms of seasons and rituals in the lives of the protagonists. This ritualization is connected with the motive of a game, which also appears in both the film and the story. The analysis proves that slight changes in this faithful adaptation open the possibility of different interpretations. Despite the political allusions in the work of Zhang Yimou, the specific style of narration allows interpreting the film in universal categories.